PENGOLAHAN LIMBAH PADAT KANTIN KABARA MENJADI BIOGAS MENGGUNAKAN 120 LITER PORTABEL BIOREAKTOR: (Studi kasus di kantin Universitas Malahayati Bandar Lampung) - Angger Faqih Arridho; Atmono; Hardoyo (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2025)
Solid waste from the Kabara canteen of Malahayati University Bandar Lampung is one of the sources of materials that can be used to produce biogas. Solid waste from the Kabara canteen that is discarded and not utilized can be used as bioenergy.This study aims to determine the production of biogas from solid waste from the Kabara canteen mixed with cow dung solution in a continuous anaerobic process using a Portable Bioreactor. This study was conducted at the Malahayati University Laboratory, Bandar Lampung from May 23, 2024 to September 30, 2024. The study was conducted on a laboratory scale with a reactor volume of 120 liters. Production is carried out continuously by entering solid waste from the Kabara canteen with cow dung solution using a ratio of 1: 1 after the reactor conditions are stable, then solid waste from the Kabara canteen with cow dung solution is entered with a debit of 26.4 kg with a time interval of 4 days with a test ratio (1: 1, 2: 1 and 3: 1) with a residence time used is 15 days. The variables measured are COD concentration, gas pressure on the Manometer and flame test. The conclusion of this study is the manufacture of environmentally friendly Portable Biogas Bioreactor using 120 liters, using solid waste from the Kabara canteen mixed with cow dung solution as a starter that can reduce COD content from 30,222, 23,111 and 21,333 mg / l and in the influent down to 11,333, 11,571 and 11,600 mg / l in the effluent, with degraded COD of 62.5%, 49.9% and 45.6%. The results of the biogas flame produced were measured on days 15, 19 and 23 that the flame was still red indicating that the methane gas content produced was still low.